Disruption of Intracellular ATP Generation and Tight Junction Protein Expression during the Course of Brain Edema Induced by Subacute Poisoning of 1,2-Dichloroethane - Wang, Gaoyang; Yuan, Yuan; Gao, Lanyue; Tan, Xiaoqiong; Yang, Guangqian; Zhao, Fenghong; Jin, Yaping (Frontiers in Neuroscience, 2018)
The aim of this study was to explore changes in intracellular ATP generation and tight junction protein expression during the course of brain edema induced by subacute poisoning of 1,2-dichloroethane (1,2-DCE). Mice were exposed to 1.2 g/m3 1,2-DCE for 3.5 h per day for 1, 2 or 3 days, namely group A, B and C. Na+-K+-ATPase and Ca2+-ATPase activity, ATP and lactic acid content, intracellular free Ca2+ concentration and ZO-1 and occludin expression in the brain were measured. Results of present study disclosed that Ca2+-ATPase activities in group B and C, and Na+/K+-ATPase activity in group C decreased, whereas intracellular free Ca2+ concentrations in group B and C increased significantly compared with control. Moreover, ATP content decreased, whereas lactic acid content increased significantly in group C compared with control. On the other hand, expressions of ZO-1 and occludin at both the protein and gene levels in group B and C decreased significantly compared with control. In conclusion, findings from this study suggest that calcium overload and depressed expression of tight junction associated proteins, such as ZO-1 and occludin might play an important role in the early phase of brain edema formation induced by subacute poisoning of 1,2-DCE.